THE ECONOMICS OF COUNTERTERRORISM: A SURVEY. (7th February 2014) - Schneider, Friedrich; Brück, Tilman; Meierrieks, Daniel
Abstract We provide a review of theoretical and empirical contributions on the economic analysis of terrorism and counterterrorism. We argue that simple rational‐choice models of terrorist behavior – in the form of cost‐benefit models – already provide a well‐founded theoretical framework for the study of terrorism and counterterrorism. We also hint at their limitations which relate to the failure of accounting for the dynamics between terrorism and counterterrorism that may produce unintended second‐order effects as well as for the costs associated with counterterrorism and its international dimension. We reevaluate previously proposed counterterrorism strategies accordingly. Finally, in the light of our findings, we discuss interesting areas of future research.